Being a Better Neighbor: A Value-Based Perspective on Negotiating Acceptability of Locally-Owned Wind Projects - van der Waal, Esther C.; van der Windt, Henny J.; Botma, Rixt; van Oost, Ellen C. J. (Sustainability, 2020)
We pose that instead of problematizing negative attitudes of local stakeholders, such as citizens and NGOs, wind energy implementers should be more focused on scrutinizing the acceptability of their projects. The emphasis in this study is on the potential for representation of local stakeholders’ values in the project design, including amongst others business model and placement. Informed by value sensitive design literature, we analyzed two contrasting, locally-owned wind projects in the Dutch province of Groningen: the implementation of mini-turbines in a national landscape and a large-scale multi MW wind project in an industrialized area close to a World Heritage nature reserve. The study analyses how the respective farmer-developers and other local stakeholders attempted to resolve or ameliorate inter- and intra-value conflicts regarding livability, economy, landscape, and nature. The value conflicts turned out to be fruitful to identifying key issues and creating more widely shared value conceptualizations and design priorities. Hence, from this study it can be concluded that value conflict can be productive if carefully unpacked and managed. Uneven power distribution among stakeholders in the planning process, overcoming incommensurability of perspectives, and creating intersubjectivity remain challenges.